Geochemistry of trace elements in the Keşan coal and its effect on the physicochemical features of ground- and surface waters in the coal fields, Edirne, Thrace Region, Turkey - Erarslan, Cemile; Örgün, Yüksel; Bozkurtoğlu, Erkan; Örgün, Tutay Yüksel; Bozkurtoğlu, Erkan (Elsevier BV, 2014)
Abstract In this study, concentration and origin of trace elements of the Kesan coals in Edirne, Thrace Basin, have been investigated in order to determine possible environmental impacts on water pollution. The coal, ground and surface waters, and clay samples were taken from the coal mining area. The concentration of trace elements in 14 coal ashes, 15 water samples, and seven clays was determined by inductively coupled plasma-mass spectrometry. Additionally 11 of these coal samples were studied by proximate and seven coal samples were also studied by X-ray diffraction analyses. The mineralogical composition of the studied coal samples is made up mainly of quartz, clay minerals, feldspar group minerals, pyrite and amorphous matter. The Kesan coal ash samples have higher average concentrations of Cr (180 ppm), Ni (192 ppm), Rb (91 ppm), and Sr (1701 ppm); average values of other trace elements are lower than the world average of brown coal ashes. The sulfur content of the Kesan coals ranges from 0.4 to 3.90% (2.02% on average). The pH values of the waters vary between 6.55 and 8.36 in coal fields, 7.21 and 7.54 in springs. The F, Cl, NO3−, SO4=, Ca, Mg, Na and K values of the waters vary between 0.11 and 0.25 mg/l, 33.49 and 52.90 mg/l, 0.05 and 59.27 mg/l, 85 and 2829 mg/l, 66 and 349 mg/l, 64 and 222 mg/l, 41 and 1187 mg/l, 2 and 13 mg/l, respectively in coal fields. Some elements are anomalous in concentrations in some water samples (e.g., Cr up to 49.6 ppb; Mn up to 1185 ppb; Fe up to 10,352 ppb; Ni up to 55.8 ppb; As up to 9.7 ppb ppb). It has been interpreted that the lower trace element concentrations in the water samples may be due to clay intercalated with coal. The clays are smectite type and they are enriched in Cr, Co, Ni, As, Sr, and Th (e.g., up to 394 ppm Cr, up to 305 ppm Ni, and up to 35.5 ppm As).